2013
DOI: 10.3389/fmicb.2013.00147
|View full text |Cite
|
Sign up to set email alerts
|

Presence of multi-drug resistant pathogenic Escherichia coli in the San Pedro River located in the State of Aguascalientes, Mexico

Abstract: Contamination of surface waters in developing countries is a great concern. Treated and untreated wastewaters have been discharged into rivers and streams, leading to possible waterborne infection outbreaks and may represent a significant dissemination mechanism of antibiotic resistance genes. In this study, the water quality of San Pedro River, the main river and pluvial collector of the Aguascalientes State, Mexico was assessed. Thirty sample locations were tested throughout the River. The main physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 76 publications
(98 reference statements)
4
29
4
Order By: Relevance
“…Antibiotic resistance-based finding of Stewardson et al, [5] study was in contrast with our results which showed the high prevalence of resistance and also antibiotic resistance genes. This part of our study was similar with those of India [28] (high prevalence of resistance against erythromycin, cephalothin, amikacin, kanamycin and gentamicin antibiotics), South Africa [29] (high presence of CITM , blaSHV and tetA antibiotic resistance genes), Korea [30] (high prevalence of resistance against ampicillin, tetracycline, streptomycin and amikacin antibiotics) and Mexico [31] (high presence of tet , blaSHV , qnr and aac ( 3 )- IV antibiotic resistance genes and also high prevalence of resistance against ampicillin, trimethoprim-sulfamethoxazole, chloramphenicol and cephalotine antibiotics). Momtaz et al, [20] reported that aac ( 3 )- IV (68.03%), sul1 (82.78%), blaSHV (56.55%), aadA1 (60.65%) and tetA (51.63%) and also resistance against tetracycline (86.88%), penicillin (100%), gentamycin (62.29%) and streptomycin (54.91%) were the most commonly reported antibiotic resistance-based finding of STEC strains of diarrheic patients which was similar to our results.…”
Section: Discussionsupporting
confidence: 85%
“…Antibiotic resistance-based finding of Stewardson et al, [5] study was in contrast with our results which showed the high prevalence of resistance and also antibiotic resistance genes. This part of our study was similar with those of India [28] (high prevalence of resistance against erythromycin, cephalothin, amikacin, kanamycin and gentamicin antibiotics), South Africa [29] (high presence of CITM , blaSHV and tetA antibiotic resistance genes), Korea [30] (high prevalence of resistance against ampicillin, tetracycline, streptomycin and amikacin antibiotics) and Mexico [31] (high presence of tet , blaSHV , qnr and aac ( 3 )- IV antibiotic resistance genes and also high prevalence of resistance against ampicillin, trimethoprim-sulfamethoxazole, chloramphenicol and cephalotine antibiotics). Momtaz et al, [20] reported that aac ( 3 )- IV (68.03%), sul1 (82.78%), blaSHV (56.55%), aadA1 (60.65%) and tetA (51.63%) and also resistance against tetracycline (86.88%), penicillin (100%), gentamycin (62.29%) and streptomycin (54.91%) were the most commonly reported antibiotic resistance-based finding of STEC strains of diarrheic patients which was similar to our results.…”
Section: Discussionsupporting
confidence: 85%
“…Isolates from poultry and rooks that displayed clinical levels of ciprofloxacin resistance linked to single or double mutations in gyrA and parC were found in our study. Strains of various animal origin with these types of mutations have been recently found worldwide (Sáenz et al, 2003; Liu et al, 2012; Castillo et al, 2013; Johnning et al, 2015; Balakrishnan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Roe et al [25] showed that the Rio Grande River, a major source of irrigation water for both the USA and Mexico, harbors MDR E. coli with a prevalence rate of 32%. Another important source of irrigation water in Mexico is the San Pedro River which was found to be contaminated by MDR E. coli with a prevalence rate of 30.6% [27]. In a study of Chigor et al [26], surface waters used for irrigation in Zaria, Nigeria were found to be contaminated with pathogenic E. coli O157:H7, which are also MDR.…”
Section: Discussionmentioning
confidence: 99%